Prospective Customer Preference Toward Service Robots: A Discrete Choice Model Approach (School of Business and Management Institut Teknologi Bandung, 2022)
Abstract. One major technological development pertains to the service robot industry. In Indonesia, the development of robots is increasing. Telkom will begin to explore new opportunities with companion robots, which can respond to and chat with humans and move around. Therefore, more analysis is needed based on market research and prospective user surveys. The present study aims to obtain information on the features of service robots significantly influencing customers’ desire to purchase them and on the types of service robots they are likely to choose. The discrete choice model method is used to understand and predict a decision from a discrete alternative, based on a set of choices constructed with the help of the Ngene software and the D-efficient design method. We processed questionnaire results using the Python-Biogeme software to look for significant attributes and their elasticity. The significant attributes of companion robots defined by T-test are basic robot look (3.86), battery life (5.45), robot price (9.16), walking-computer look (6.10), and robot weight (8.38). The suggested strategy, among the three types of companion robots, is to focus on the personal assistant robot with the highest T-test score while paying attention to the resources a company already has.Keywords: Service Robot, Discrete Choice Model, Significant Attribute, Elasticity